Summary Procedure before the Strasbourg Court under Article 28(1)b of the European Convention on Human Rights: Judicial Economy under Scrutiny (Polish Yearbook of International Law, 2018)
This article critically evaluates the summary procedure introduced by Protocol No. 14 to the European Convention on Human Rights, adopted within the reform of the European Court of Human Rights system. The summary procedure, now set out in Art. 28(1)b of the Convention, was instituted in order to facilitate expediency and to reduce the case load of the Court. This article argues that while judicial economy is a legitimate goal, the summary procedure under Art. 28(1)b has considerable deficiencies that undermine some of the systemic goals and core values of ECHR law. There is a manifest lack of remedies vis-à-vis the choice of the procedure, choice of applicable law, and no appeals against final decisions rendered in the course of the summary procedure. Notably, the concept of “well-established case-law” seems to be neither clear nor reliable, as evidenced in the cases analysed in the article. These cases, which involve the issue of socially- owned property in Serbia, serve to demonstrate some of the significant errors in interpretation and decision-making which can result from application of the summary procedure.